2017
DOI: 10.17679/inuefd.354142
|View full text |Cite
|
Sign up to set email alerts
|

İlkokul Öğrencilerinin Çevre Sorunları Ve Çevre Eğitimine Yönelik Algıları

Abstract: The aim of the study was to determine the perceptions of primary school students about environmental problems and environmental education. The working group is composed of 50 students who are enrolled in a public school in Yeniçağa. A structured interview form was used as a data collection tool. According to research findings, students expressed the concept of environment as life friendly, home, oxygen, life, living space, tree, world and nature. The students expressed the garbage wastes, the destruction of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
0
5
0
6
Order By: Relevance
“…According to the research, it has been revealed that the students see the environment as nature, tree, life, greenery and the world. According to the research carried out by Ertürk (2017), students support the result of this study by expressing the environment as friend, home, oxygen, life, living area, tree, world and nature.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…According to the research, it has been revealed that the students see the environment as nature, tree, life, greenery and the world. According to the research carried out by Ertürk (2017), students support the result of this study by expressing the environment as friend, home, oxygen, life, living area, tree, world and nature.…”
Section: Discussionmentioning
confidence: 67%
“…It has been concluded that some tasks fall on people such as saving water, keeping the environment clean, protecting nature, planting trees, collecting garbage after picnic, separating the recyclable materials, saving electricity, using electric vehicles instead of gasoline vehicles to solve environmental problems. Ertürk (2017) It is seen that students support the result of this study by expressing garbage waste, cutting down trees, soil pollution, throwing garbage to water, throwing waste batteries into the environment, air and sound pollution, forest fires as environmental problems.…”
Section: Discussionmentioning
confidence: 75%
“…Nitekim, çevre gezileri, doğa yürüyüşleri, kamplar gibi etkinliklerin bireylerin çevreye karşı duyarlıklarını arttırdığı, davranış ve sosyal ilişkilerini de etkilediği belirtilmektedir (Palmberg & Kuru, 2000;Oweini & Houri, 2006). Okullarında çevre projelerinin, çevre eğitimiyle ilgili tiyatroların, çevre ile ilgili müzik yayınlarının yapılması, doğa defterlerinin oluşturulması, çevre temizliği ile ilgili yarışmaların düzenlemesi, çevre dergisinin oluşturulması gibi faaliyetlerin ilkokul öğrencilerinin çevresel algılarına katkı sağladığı görülmektedir (Ertürk, 2017).…”
Section: Tablounclassified
“…İlkokul 4. sınıf öğrencilerinin çevre sorunları ve çevre eğitimine yönelik algıları incelendiğinde öğrencilerin Dünya'da ve Türkiye'de en fazla yaşanan çevre sorununun çöp atıkları olduğunu ve bu sorunun geri dönüşüm uygulamaları ile çözülebileceğini ifade ettikleri görülmüştür (Ertürk, 2017). Benzer şekilde ilköğretim 8. sınıf öğrencileri için çevre sorunları genel olarak çöp odaklı olmasına karşın sadece bir öğrencinin geri dönüşümün olduğu bir çevrede yaşamak istediğini ifade etmesi dikkat çekicidir (Yardımcı ve Bağcı-Kılıç, 2010).…”
Section: Introductionunclassified